Production of extracellular acid proteases by Aspergillus clavatus - Tremacoldi, C. R.; Watanabe, N. K.; Carmona, E. C. (Kluwer Academic Publ, 2004)
The production of extracellular acid proteases from Aspergillus clavatus was evaluated in a culture filtrate medium, with different carbon and nitrogen sources. The fungus was cultivated at three different temperatures during 10 days. The proteolytic activity was determined on haemoglobin pH 5.0 at 37 degreesC. The highest acid proteolytic activity (80 U/ml) was observed in culture medium containing glucose and gelatin at 1% (w/v) at 30 degreesC at the third day of incubation. Cultures developed in Vogel medium with glucose at 2% (w/v) showed at about 45% of proteolytic activity when compared to the cultures with 1% of the same sugar. The optimum pH of enzymatic activity was 2.0 and the enzyme was stable at pH values ranging from 2.0 to 4.0. The optimum temperature was 40 degreesC and the half-lives at 40, 45 and 50 degreesC were 30, 10 and 5 min, respectively.
Keywords: acid protease; Aspergillus clavatus; enzyme characterization; optimization; production